2023
DOI: 10.3390/ijms24065693
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Aspects of Benzene Degradation over TiO2-N and Composite Fe/Bi2WO6/TiO2-N Photocatalysts under Irradiation with Visible Light

Abstract: In this study, composite materials based on nanocrystalline anatase TiO2 doped with nitrogen and bismuth tungstate are synthesized using a hydrothermal method. All samples are tested in the oxidation of volatile organic compounds under visible light to find the correlations between their physicochemical characteristics and photocatalytic activity. The kinetic aspects are studied both in batch and continuous-flow reactors, using ethanol and benzene as test compounds. The Bi2WO6/TiO2-N heterostructure enhanced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Photocatalysis serves as a remarkable solution for various environmental challenges. 14,211 The conventional semiconductors employed as photocatalysts include ZnO, 212,213 TiO 2 , 214,215 CdS, 216,217 etc. , which play a significant role in the degradation of environmental contaminants.…”
Section: Photo Catalysis Mechanisms: Understanding the Science Behind...mentioning
confidence: 99%
“…Photocatalysis serves as a remarkable solution for various environmental challenges. 14,211 The conventional semiconductors employed as photocatalysts include ZnO, 212,213 TiO 2 , 214,215 CdS, 216,217 etc. , which play a significant role in the degradation of environmental contaminants.…”
Section: Photo Catalysis Mechanisms: Understanding the Science Behind...mentioning
confidence: 99%
“…Recent advancements in the preparation of TiO2 can potentially broaden its applications in photocatalytic processes. Modified TiO2 with an extended action spectrum shows promise as a photocatalyst for efficiently degrading pollutants under visible light [35].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these challenges, photocatalysis, a promising "green technique", is being continuously explored for the removal of organic pollutants from aqueous media via photochemical reactions using semiconductor material/s [6]. Moreover, photocatalysis is regarded as a renewable technique for energy conversion and environmental restoration that involves oxidation and reduction reactions initiated by photogenerated charge pairs, i.e., electrons (e − ) and holes (h + ), under light irradiation [7,8]. The first study related to the photodegradation of organic pollutants was reported by Carey et al in the presence of a TiO 2 semiconductor photocatalyst in an aqueous solution [9].…”
Section: Introductionmentioning
confidence: 99%